2020
DOI: 10.3390/dj8010019
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Facilitated Aesthetic Orthodontic Treatment with Clear Aligners and Minimally Invasive Corticotomy

Abstract: Accelerating orthodontic tooth movement has become a topical issue and the corticotomy seems to be the only effective and safe technique reported in the literature. Simultaneously, aesthetic orthodontic treatment with removable clear aligners has become commonly requested. The aim of this paper is to illustrate the management of facilitated aesthetic orthodontic treatment, a combined approach including piezocision corticotomy and clear aligners for orthodontic treatment. Orthodontic planning for traditional cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Clear aligners are an orthodontic system that has been introduced as an answer to this request. Recent systematic reviews have shown that orthodontic treatment with clear aligners has been effective in obtaining a proper alignment and leveling of the dental arches during the last decade, even in more complex cases and in children or adolescents [ 3 , 4 ]. Moreover, compared to treatment with fixed appliances, orthodontic treatment with removable appliances and especially clear aligners has shown better preservation of periodontal indexes and oral hygiene, related to a lower risk of periodontal damage or enamel demineralization and caries [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clear aligners are an orthodontic system that has been introduced as an answer to this request. Recent systematic reviews have shown that orthodontic treatment with clear aligners has been effective in obtaining a proper alignment and leveling of the dental arches during the last decade, even in more complex cases and in children or adolescents [ 3 , 4 ]. Moreover, compared to treatment with fixed appliances, orthodontic treatment with removable appliances and especially clear aligners has shown better preservation of periodontal indexes and oral hygiene, related to a lower risk of periodontal damage or enamel demineralization and caries [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stepwise shape changing property, this material was proposed to be used for the fabrication of orthodontic aligners, as it may successfully be used to overcome the rate-limiting staging of conventional aligners, in a way that one aligner may be able to replace three subsequent conventional aligners. Consequently, the number of aligners used per treatment could be reduced, beside saving money and time, especially for long and more complex therapies such as molar distalization and severe open/deep bite correction that are frequently performed nowadays [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from educational purposes, these models can be used when resective surgeries have to be performed in highly anatomically sensitive areas, such as neurologic passage landmarks and maxillary sinuses. Preventive planning is performed on the virtual 3D model [6], while planning is then performed on the physical model before the actual intervention takes place on the patient. Surgeons' opinions regarding the benefits of stereolithographic model use as a pre-surgical tool confirm the optimization of the diagnostic as well as surgical act by means of reducing operating room time, improving visualization of the patient's unique structures, and increasing pre-surgical commitment after surgical rehearsal on 3D models [5].…”
Section: Of 10mentioning
confidence: 99%